Contribution of Personnel Management to the Generation of Innovation Capabilities in Medium and Large Companies in Colombia - Rubio-Rodríguez Gustavo Adolfo; Ortiz Yeison Farid Méndez; Cardoso Elizabeth Palma; Perdomo Efraín Enrique Granados (Studies in Business and Economics)
The purpose of this research is to determine the contribution of human resources management in the development of innovative capabilities in medium and large companies in the city of Ibagué, Colombia. The study is exploratory and uses a mixture of quantitative techniques for its development, being non-experimental. The study population is made up of 107 medium-sized companies and 23 large companies in the city of Ibagué. Since the population to be studied is finite and known, a stratified random probability sampling with finite population adjustment is carried out, since the possibility of selecting one or another element is equal. In addition, the aim is to ensure that all the units of analysis (medium and large companies) are duly represented. The results showed that businessmen understand the importance of human resources management and innovation for the organization; most managers recognize that, through human resources management, employees are capable of innovating in all areas in which they work. However, their development has been stagnated in some cases due to lack of management within the organization itself.